Well-defined silica supported aluminum hydride: another step towards the utopian single site dream?1. Issue 10 (14th October 2015) - Werghi, Baraa; Bendjeriou-Sedjerari, Anissa; Sofack-Kreutzer, Julien; Jedidi, Abdesslem; Abou-Hamad, Edy; Cavallo, Luigi; Basset, Jean-Marie
<x xml:space="preserve">Abstract</x> Reaction of triisobutylaluminum with SBA15700 at room temperature occurs by two parallel pathways involving either silanol or siloxane bridges.